Analisis Filosofis Kurikulum Merdeka: Implikasi bagi Pengajaran Bahasa Inggris - Suhendra, Ade; Aprison, Wedra; Yanti, Fitri; Bayu, Eka Pasca Surya (El-Rusyd, 2025)
This article aims to examine the philosophical foundations of the Merdeka Curriculum within the context of Islamic education and to explore their implications for English language teaching. The study focuses on selected philosophical orientations namely pragmatism, constructivism, and existentialism and considers their relevance to educational values commonly discussed in Islamic educational thought. A qualitative approach was employed through a literature-based study, drawing on policy documents, curriculum guidelines, and relevant philosophical and educational literature. The analysis suggests that the Merdeka Curriculum reflects philosophical tendencies that may support more contextual, dialogic, and learner-centered approaches to English language teaching, particularly in relation to communicative competence, the role of teachers, learning media, assessment practices, and student creativity. At the same time, the literature also points to potential limitations, including variations in teacher preparedness, unequal access to learning resources, and established evaluation cultures that may affect classroom implementation. The article implies that a reflective engagement with philosophical foundations especially when situated within Islamic educational perspectives may help educators approach the Merdeka Curriculum more critically, so that changes in English language instruction are not limited to technical adjustments but also involve broader shifts in educational orientation.